Effect of Drum-Drying Conditions on the Content of Bioactive Compounds of Broccoli Pulp - Mahn-Osses, A; Quintero-Suarez, J (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
This work studied the effect of drum-rotation frequency, drum temperature, and water-to-pulp ratio in a double-drum drier on the content of sulforaphane, glucoraphanin, total phenolic compounds, ascorbic acid, and antioxidant activity of broccoli pulp through a multilevel factorial design with one replicate. Drum-drying conditions did not significantly affect sulforaphane content, unlike glucoraphanin, however the poor adherence of broccoli pulp resulted in a final product with undefined shape and heterogeneous color. On the other hand, antioxidant activity was unevenly affected by drying conditions; however, drum-rotation frequency affected it in the same way that phenolic compounds and ascorbic acid, showing a concordant behavior. The ascorbic acid content decreased significantly after drying, and it was highly dependent on the experimental factors, resulting in a regression model that explained 90% of its variability. Drum-rotation frequency of 5 Hz, drum temperature of 125 ◦C, and water-to-pulp ratio of 0.25 resulted in an apparent increase of sulforaphane and phenolic compounds content of 13.7% and 47.6%, respectively. Drum drying has great potential to fabricate dehydrated broccoli-based foods with functional properties. Besides, since drum drying has low investment and operation costs, it represents a very attractive option for the industrialization of broccoli derivatives. © 2020 by the authors. Licensee MDPI, Basel, Switzerland. This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (http://creativecommons.org/licenses/by/4.0/).